Survival of patients with de novo metastatic breast cancer - Leite, Fernanda Perez Magnani; Fernandes, Gisele Aparecida; Curado, Maria Paula; Sanches, Solange Moraes; Felippe, Livia Prôa; Makdissi, Fabiana Baroni Alves (Mastology, 2024)
Introduction: For the 2020-2022 trieniumm more than 2 million cases of breast cancer were estimated worldwide. De novo metastatic breast cancer is so called when metastasis is diagnosed at the same time as the primary tumor. It affects approximately 3.5 to 10% of breast cancer patients and only 25% of these will be alive after 5 years. Methods: We conducted a retrospective cohort study of women with de novo metastatic breast cancer treated at a single center from January 1, 2000 to December 31, 2012. Cases were identified in the Hospital Cancer Registry. Overall survival (OS) was estimated at 5 years with the Kaplan-Meier product limit, and the log-rank test was used to test differences between curves; Cox multiple regression and all tests were considered significant with p<0.05. Results: Of the 265 patients in the study, the estimated 5-year OS was 31.3%. There was a difference in survival according to the following: age group (p<0.046); having had breast surgery (p<0.001); having undergone chemotherapy simultaneously with radiotherapy, hormone therapy, targeted therapy or surgery (p<0.088); use of exclusive or multimodal hormone therapy (p<0.001); education (p<0.001); luminal tumors (p<0.003); and being treated between 2006 and 2012 (p=0.043). In the multiple model adjusted by age group and education, the following factors remained as predictors of a better prognosis: having undergone surgery (hazard ratio — HR=0.46, 95% confidence interval — 95%CI 0.32–0.66); luminal tumors (HR=0.34, 95%CI 0.23–0.50); and targeted therapy (HR=0.27, 95%CI 0.15–0.46). Conclusion: The risk of death in patients with de novo metastatic breast cancer was lower than in those undergoing local surgical treatment as part of multimodal treatment, as well as the luminal molecular subtype and the introduction of better systemic treatment strategies, such as target.